Reply to BUGC's letter asking BRACU for sharing Contractor’s All Risks (CAR) insurance premium - Brac University (Brac University, 2023)
This record consists of general correspondence regarding reply to BUGC's letter asking BRACU for sharing Contractor’s All Risks (CAR) insurance premium of BRAC University new campus project.